Pengembangan E-book Berbasis Discovery Learning Terintegrasi Keterampilan 4C Untuk Pembelajaran Fisika SMA - Yosi Dwi Anggreni; Yohandri Yohandri (JURNAL EKSAKTA PENDIDIKAN (JEP), 2022)
The problem found in the field is that the e-books available in schools do not contain the 4C skills that students should have in the 21st century. In addition, the existing e-books have not shown any learning model syntax that is in accordance with the 2013 curriculum. The e-books used have not been able to involve students effectively. directly in finding the concept of learning. So, it takes a discovery learning-based e-book that is integrated with 4C skills. The purpose of this research is to produce an e-book based on discovery learning integrated 4C skills in physics learning with valid, practical, and effective categories. This type of research is research and development. The e-book development uses the ADDIE development model which consists of the analysis, design, development, implementation, and evaluation stages. Research data in the form of preliminary study data, validation, practicality, and effectiveness. The research instrument consisted of a preliminary questionnaire, validation instrument, practicality instrument, and effectiveness instrument. Data analysis was carried out using the ADDIE development method which consisted of analysis, design, development, implementation and evaluation, including aspect of knowledge, attitudes, and 4C skills; critical thinking skills, creative thinking skills, and communication skills. Based on the research conducted, it can be concluded that the physics e-book based on discovery learning integrated 4C skills is valid, practical and effective. so that it can be used to improve student learning outcomes.